Analisis Du Pont dan Economic Value Added Dalam Menilai Kinerja Keuangan Perusahaan Sub Sektor Rokok - Rusdi Abdulkarim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This study aims to determine the analysis of Du Pont and Economic Value Added to assess the financial performance of the Cigarette Sub-Sector Companies that Go Public on the Indonesia Stock Exchange. To analyze the Du Pont System using the ratio of profit margin, Asset Turnover, Return of Assets, and Return of Equity. The results show that the Return of Assets from 2016 to 2020. is below the standard Return of Assets ratio. the company has not been effective in managing total assets to generate net income. Economic Value Added from 2018 to 2020 has an average negative value, which means the company is not successful in creating added economic value.